Regularisation of singular 2D linear models by state-feedbacks - Kaczorek, Tadeusz (1932- ) (Zielona Góra: Uniwersytet Zielonogórski)
New necessary and sufficient conditions are established under which the singular 2D first Fornasini-Marchesini model and the singular 2D Roesser model can be regularised by state feedbacks. Some procedures for computation of the respective feedback matrices are given and illustrated by numerical examples.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka